Avoiding the Pestilence of the State: Some Thoughts on Niche Construction, Heritage, and Sacred Waterworks. Issue 1 (14th December 2017) - Wengrow, David
Abstract : The egalitarian character of traditional irrigation ( subak ) systems in Bali has been widely documented and discussed by anthropologists, historians, and archaeologists. In a recent study, Stephen Lansing and Karyn Fox considered how the principles of niche construction theory might help to understand the genesis of these systems, as well as certain of their institutional characteristics. Here I discuss how this approach might be extended, to include the relationship between subak systems and the hierarchical organization of the Balinese state, within which they exist. Just as the logistics of subak irrigation work to maintain a symbiosis between rice farmers and the non-human predators (e.g. crop-pests) which surround them, so the ritual elaboration of the agrarian calendar works as a kind of cultural camouflage against the parasitical interests of the state. In theory, these ecological and institutional dimensions of subak may seem to pertain to quite separate spheres of Balinese life. In practice, I suggest, they are intertwined aspects of a single system, which allowed the subak to survive from their origins in the 11 th century AD, down to their recent inscription on the UNESCO World Heritage List.